2021
DOI: 10.1167/iovs.62.6.19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PROM1 p.Arg373Cys Variant in a Cohort of Chinese Patients: Macular Dystrophy Plus Peripheral Bone-Spicule Degeneration

Abstract: The PROM1 p.Arg373Cys variant has been reported to cause dominant Stargardt disease, cone-rod dystrophy, and occasionally retinitis pigmentosa. This study aimed to evaluate the common phenotype associated with this variant in Chinese patients. METHODS.Variants in PROM1 were collected from in-house exome data. Potential pathogenic variants were selected, verified, and then confirmed by Sanger sequencing and co-segregation analysis. Ocular phenotypes were reviewed and further clarified by ophthalmologic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…These findings indicate a considerable prevalence of autosomal dominant PROM1 p.R373C variants within Korean patients of PROM1-related IRD. Interestingly, according to previous reports, the p.R373C variant was found in six out of eight Japanese families with PROM1-related IRD 18 and in four out of seven Chinese families with PROM1-related IRD 19 , which closely aligns with the results of the present study. These findings suggest a higher proportion of autosomal dominant PROM1 p.R373C variants in Asian populations than in Western populations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings indicate a considerable prevalence of autosomal dominant PROM1 p.R373C variants within Korean patients of PROM1-related IRD. Interestingly, according to previous reports, the p.R373C variant was found in six out of eight Japanese families with PROM1-related IRD 18 and in four out of seven Chinese families with PROM1-related IRD 19 , which closely aligns with the results of the present study. These findings suggest a higher proportion of autosomal dominant PROM1 p.R373C variants in Asian populations than in Western populations.…”
Section: Discussionsupporting
confidence: 93%
“…Although studies have investigated PROM1-related retinal degeneration in various populations, few have focused on the genetic variants and clinical characteristics of PROM1-associated retinal degeneration within the Asian population 18 , 19 . Asian populations have a distinct genetic architecture influenced by unique ancestral lineages; therefore, it is crucial to understand the distribution of the variants and their effect on the clinical manifestation of IRDs within this population.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Luo et al. 2021; 2021a, b, c). However, the findings of this study showed that patients with PRPF gene‐related ADRP had more severe macular involvement (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). In the studies of Witkin et al (2006) and Birch et al (2013), it was found that the thickness of the outer retinal and the width of EZ could related RP are mainly distributed in the far-peripheral retina (Wang et al 2021c). In the current study, through a wide-field SLO examination, it was found that bone spicule-like pigmentation in patients with ADRP related to PRPF8 and PRPF31 was observed from the mid-to the farperipheral retina (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that a single heterozygous variant of the autosomal recessive genes may cause ad-related retinopathy, such as, the heterozygous p.(Arg373Cys) variant in PROM1 , 42 44 heterozygous p.(Asp477Gly) variant in RPE65 , 45 47 and heterozygous substitution of p.Arg838 in GUCY2D . 48 51 Similarly, heterozygous frameshift variants of RDH12 have been identified in patients with adRP.…”
Section: Discussionmentioning
confidence: 99%